Zeeman structure of red lines of lanthanum observed by laser spectroscopy methods. (November 2017) - Sobolewski, Ł.M.; Windholz, L.; Kwela, J.
Highlights: New metod of Lande gJ factors measurement was used for observation of La I spectra. New experimental gJ factors have been determined. Hfs data for La I levels have been tested and corrected. Abstract: Laser Induced Fluorescence (LIF) Spectroscopy and Optogalvanic (OG) Spectroscopy were used for the investigation of the Zeeman hyperfine (hf) structures of 27 spectral lines of La I in the wavelength range between 633.86 and 667.54 nm. As a source of free La atoms a hollow cathode discharge lamp was used. Spectra were recorded in the presence of a relatively weak magnetic field (about 800G) produced by a permanent magnet, for two linear polarization directions of the exciting laser beam. As a result of the measurements, we determined for the first time the Landé gJ - factors of 18 levels of La I. The Landé gJ - factors of 12 other levels were re-investigated and determined with higher accuracy.